MENGENALKAN ALAT MUSIK TRADISIONAL MELALUI KEGIATAN EKSTRAKURIKULER SULING BAMBU DI SD INPRES RUTOSORO - Dedy Setyawan (Yayasan Akrab Pekanbaru, 2018)
This study aims to introduce traditional musical instruments to learners and as a cultural arts venue through extracurricular activities of music. Extracurricular music organized more refers to the learning of traditional musical instruments, namely the art of bamboo flute music. The research method used is field research (field research), because this research uses descriptive research method of analysis with a qualitative approach. Research data obtained from observation, interview, and documentation. The subjects in this study are 4th and 5th grade students of SD Inpres Rutosoro, amounting to 30 students. The results of this study indicate that the implementation of extracurricular activities of bamboo flute music in general has been good, but the limited time provided not all the material activities of extracurricular music bamboo flute delivered as a whole. However, when viewed from the results of activities and exercises of extracurricular participants, it can be concluded that the purpose of this activity can be achieved. Keywords: Extracurricular, Traditional Music, Bamboo Flute.